Oxygen uptake (V˙ O2) and pulmonary ventilation (V˙ E) during military surface fin swimming in a swimming flume: Effects of surface immersion - Castagna, Olivier; Blatteau, Jean-Eric; Druelle, Arnaud; Amara, Jordan; Lacour, Jean-René (Frontiers in Physiology, 2023)
Introduction: During military fin swimming, we suspected that oxygen uptake (V ̇O2) and pulmonary ventilation (V ̇E) might be much higher than expected. In this framework, we compared these variables in the responses of trained military divers during land cycling and snorkeling exercises. Methods: Eighteen male military divers (32.3 ± 4.2 years; 178.0 ± 5.0 cm; 76.4 ± 3.4 kg; 24.1 ± 2.1 kg.m-2) participated in this study. They performed two test exercises on two separate days: a maximal incremental cycle test (land condition), and an incremental fin swimming (fin condition) in a motorized swimming flume. Results: The respective fin and land V ̇O2max were 3701 ± 39 mL.min-1 and 4029 ± 63 mL.min-1 (p = 0.07), these values were strongly correlated (r2 = 0.78 p < 0.01). Differences in V ̇O2max between conditions increased relative to land V ̇O2max (r2 = 0.4 p = 0.01). Fin V ̇Emax values were significantly lower than land V ̇Emax values (p = 0.01). This result was related to both the significantly lower fin Vt and f (p <0.01 and < 0.04, respectively). Consequently, the fin ( V) ̇Emax/V ̇O2max ratios were significantly lower than the corresponding ratios for land values (p< 0.01), and the fin and land V ̇Emax were not correlated. Other parameters measured at exhaustion - PaO2, PaCO2, and SO2 - were similar in fin and land conditions. Furthermore, no significant differences between land and fin conditions were observed for peak values for heart rate, blood lactate concentration, and respiratory exchange ratio R. Conclusion: Surface immersion did not significantly reduce the V ̇O2max in trained divers relative to land conditions. As long as V ̇O2 remained below V ̇O2max, the V ̇E values were identical in the two conditions. Only at V ̇O2max was V ̇E higher on land. Although reduced by immersion, V ̇Emax provided adequate pulmonary gas exchange during maximal fin swimming.